Best Answer

This expression can be factored.

ab + 3a + b2 + 3b = a(b + 3) + b(b + 3) = (a + b)(b + 3)

Q: Ab plus 3a plus b squared plus 3b?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

0

4

(b-c)(a+b)-ac

= (a + b)2 or (a + b)(a + b) (a + b)(a + b) using the FOIL method yields: [multiplying {First Outer Inner Last} and summing the products] = a.a + a.b + b.a + b.b = a2 + ab + ab + b2 = a2 + 2ab + b2

The problem here is nobody knows if "ay squared" is (ay)2 or ay2 etc. To solve a mathematical problem it must be set out mathematically or nobody knows your intention. Here is a sort of mathematical statement which is unclear, and although it ends in a question mark, nobody knows what the question is, even if you do. Try again and people will do their best to answer it. I read the question as: x2y2 + ay2 + ab + bx2 ? But what is required to be done with it?

Related questions

a(b+3)+b(b+3)

(a + 3)( b + 2)

That factors to (b + 3)(a + c)

The GCF is a.

ab + 2a + 3b + 6

(a + x^2)(b + y^2)

b2 + ab - 2 - 2b2 + 2ab = -b2 + ab - 2 which cannot be simplified further.

0

(a+b)(a squared-ab+b squared)

x2y + axy + abx + a2b Factor by grouping. xy(x + a) + ab(x + a) (xy + ab)(x + a)

a(3+b)+c(3+b) * * * * * This is easy to finish: . . . = (a + c)(3 + b).

That factors to (a + 1)(a + b) a = -1, -b b = -a